ANTESEDEN KINERJA KARYAWAN: REWARD, PUNISHMENET DAN PENGAWASAN - Joko Suyono; Damarsari Ratnasahara Elisabeth; Wahyu Eko Pujianto; Ayu Lucy Larassaty (GREENOMIKA, 2022)
This research was conducted at an outsourcing company in Surabaya with the aim of knowing the effect of reward, punishment and supervision both simultaneously and partially on employee performance, and also to find out which variable among reward, punishment and supervision variables has a dominant effect on employee performance. The population in this study were employees of outsourcing companies in Surabaya as many as 72 people. The sampling technique used was total sample, meaning that the entire population in this study was taken as sample. While the data collection technique used a questionnaire with a Likert scale with five answer choices. The method of analysis used multiple linear regression analysis. The results of the study indicate that reward, punishment and supervision simultaneously affect employee performance simultaneously and partially. Punishment has a dominant effect on employee performance.